Chelated Minerals and Limestone Particle Sizes on Performance and Bone Quality of Brown-Egg Layers - Cordeiro,CN (2017)
ABSTRACT This study aimed to evaluate productive performance, egg quality, and bone quality of commercial brown-egg layers fed diets containing organic and inorganic minerals and three limestone particle sizes. A total of 288 birds at 64 weeks of age were distributed in a completely randomized design in a 2 × 3 factorial arrangement (two mineral sources and three limestone particle sizes) and eight replicates. The experiment lasted 112 days, divided into four periods. The following treatments were tested: T1 = inorganic minerals + 100% fine limestone; T2 = inorganic minerals + 50% fine limestone + 50% coarse limestone; T3 = inorganic minerals + 100% coarse limestone; T4 = inorganic + organic minerals + 100% fine limestone; T5 = inorganic + organic minerals + 50% fine limestone + 50% coarse limestone; and T6 = inorganic + organic minerals +100% coarse limestone. There was no significant interaction effect between the studied factors on any of the variables. No significant effect of the types of mineral mixes or limestone particle sizes were observed on the performance, egg quality, or bone quality variables evaluated. In conclusion, organic or inorganic minerals associated with limestone in fine, medium, or coarse particle sizes can be used in diets for brown-egg layers without affecting their productive performance, egg quality, or bone quality.